Keterlibatan Crisis Management Initiative (CMI) dalam Transformasi Konflik Aceh - Imran, A. M. Ali; Wicaksono, Arief (Journal of International and Local Studies, 2024)
In a conflict, the presence of a third party is required to act as a mediator if a conflict cannot be resolved by the two (or more) parties involved in the conflict. The presence of a third party as a mediator and facilitator is sometimes accompanied by implicit elements of interest behind their involvement. This research is descriptive-qualitative, based on previous research, books, and journals similar to the primary data sources. The author will sort, elaborate, analyze and conclude the facts related to CMI's interests in its involvement in the RI-GAM conflict. In this research, it is proven that CMI is a third-party actor whose involvement as a mediator has more or less had a positive political and economic impact on relations between Indonesia as one of the conflict actors and Finland, which incidentally is the country of origin of CMI. As explained in this research, CMI's involvement led to the birth of collaborations between Indonesia and Finland. This political interest also does not escape the essential roles of the international community, which is a supporting element with CMI in resolving the Aceh conflict.